Overcoming digital stress through new work environment design - Lubis, Fatimah Malini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Advances in digital technology have significantly changed the dynamics of the workplace, improving efficiency while creating new challenges for workers' well-being. One of the main challenges is digital stress, which is psychological pressure that arises due to excessive use of technology in the work environment. This stress can be caused by information overload, the expectation to always be online, and the imbalance between work and personal life. This research aims to explore how innovative work environment design can help reduce digital stress in workers. The method used in this study is a literature study by analyzing various previous studies relevant to this topic. Data sources come from academic journals, books, and research reports that discuss digital stress, worker welfare, and work environment design. The results of the study show that ergonomic work environment design, the implementation of work flexibility policies, reduction of excess technology exposure, and the integration of more humane technology can significantly reduce psychological pressure due to the use of digital technology. In addition, a work environment that supports work-life balance, such as the provision of relaxation areas, flexible workspaces, and restrictions on digital communication after hours, has also proven effective in improving workers' welfare. This research emphasizes that designing a work environment that is more adaptive to the psychological and physical needs of workers can be an effective solution in overcoming digital stress in the digital era. Therefore, organizations and companies are advised to adopt more worker-oriented workplace policies and designs.